The anticoagulation choices of internal medicine residents for stroke prevention in non-valvular atrial fibrillation. Issue 1100 (15th June 2016) - Moulson, Nathaniel; McIntyre, William F; Oqab, Zardasht; Yazdan-Ashoori, Payam; Quinn, Kieran L; van Oosten, Erik; Hopman, Wilma M; Baranchuk, Adrian
ABSTRACT: Purpose of the study: To explore the oral anticoagulation (OAC) prescribing choices of Canadian internal medicine residents, at different training levels, in comparison with the Canadian Cardiovascular Society (CCS) guidelines for non-valvular atrial fibrillation (NVAF). Study design: Cross-sectional, web-based survey, involving clinical scenarios designed to favour the use of non-vitamin K antagonists (NOACs) as per the 2014 CCS NVAF guidelines. Additional questions were also designed to determine resident attitudes towards OAC prescribing. Results: A total of 518 internal medicine responses were analysed, with 196 postgraduate year (PGY)-1s, 169 PGY-2s and 153 PGY-3s. The majority of residents (81%) reported feeling comfortable choosing OAC, with 95% having started OAC in the past 3 months. In the initial clinical scenario involving an uncomplicated patient with a CHADS2 score of 3, warfarin was favoured over any of the NOACs by PGY-1s (81.6% vs 73.9%), but NOACs were favoured by PGY-3s (88.3% vs 83.7%). This was the only scenario where OAC choices varied by PGY year, as each of the subsequent clinical scenarios residents generally favoured warfarin over NOACs irrespective of level of training. The majority of residents stated that they would no longer prescribe warfarin once NOAC reversal agents are available, and residents felt risk of adverse events was the most important factor when choosing OAC. Conclusions: Canadian internal medicine residents favoured warfarin over NOACs for patients with NVAF, which is in discordance with the evidence-based CCS guidelines. This finding persisted throughout the 3 years of core internal medicine training.